The Effect of Educational Robotics Applications on Students' Academic Achievement and Problem-Solving Skills in Science Education - Abdullah Koray; Behice Hilal Uzuncelebi (Journal of Education in Science, Environment and Health)
The study explored the effects of robotic-assisted applications on the variables of academic achievement and problem-solving skills in the “Propagation of Light” unit of the 5th grade science course. The study employed the pretest-posttest control group design, one of the quasi-experimental methods. The study sample consist of 36 5th grade students attending a public school in Turkey located in a district center in the Western Black Sea region. The study was carried out in a six-week period in the 2019-2020 academic year, and 19 of the students were selected as the control and 16 as the experimental group. Robotic supported activities were applied to the students in the experimental group, and the activities prescribed by the Science Curriculum were applied to the students in the control group. Open-ended and closed-ended “Academic Achievement Test” and “Problem-Solving Skills Test” were used as pretest and posttest in both groups. The data were analyzed using the independent samples t-test. The study results revealed that the academic achievement and problem-solving skills of the students in the experimental group, in which robotic-assisted activities were used, were significantly higher in both tests compared to the students in the control group.